LATE PLEISTOCENE RODENTS (MAMMALIA: RODENTIA) FROM THE BARANICA CAVE NEAR KNJAZEVAC (EASTERN SERBIA): SYSTEMATICS AND PALAEOECOLOGY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Baranica is a cave in the Balkan mountain range in the eastern part of Serbia. It contains four layers of sediments of Quaternary age. The Upper Pleistocene deposits (layers 2-4) have yielded a rich and diverse assemblage of vertebrate fauna, including fish, amphibians, reptiles, birds, and small and large mammals. In this work, preliminary results of a study of the rodent fauna from the Upper Pleistocene deposits of the Baranica Cave (Knjazevac, eastern Serbia) are presented. The fossil material comes from the 1995 archaeological excavation. The remains of 10 rodent species are described herein: Spermophilus cf. citelloides, Castor fiber, Sicista subtilis, Cricetulus migratorius, Cricetus cricetus, Mesocricetus newtoni, Apodemus ex gr. sylvaticus-flavicollis, Spalax leucodon, Dryomys nitedula, and Muscardinus avellanarius. Along with eight vole species, this makes altogether 18 species of rodents found in this locality. Both layers 2 and 4 (layer 3 is very poor in fossils) have yielded a rodent fauna typical for the cold periods of the Late Pleistocene on the Balkan Peninsula, with a prevalence of open and steppe inhabitants, but some forest dwellers were also present. The assemblages from these layers are similar, but there are some differences in the composition of the fauna, which may indicate a slight shift towards drier conditions. They have also been compared to rodent associations from some Serbian and Bulgarian localities of the same age and their similarities and differences are discussed. SHORT NOTE-NOTA BREVE
Keywords: Pleistocene; Quaternary; Rodents; Small mammals; Serbia; Balkan Peninsula